Do Ionic Liquids Exhibit the Required Characteristics to Dissolve, Extract, Stabilize, and Purify Proteins? Past-Present-Future Assessment - Bharmoria, Pankaj; Tietze, Alesia A; Mondal, Dibyendu; Kang, Tejwant Singh; Kumar, Arvind; Freire, Mara G (Chemical Reviews, 2024)
Proteins are highly labile molecules, thus requiring the presence of appropriate solvents and excipients in their liquid milieu to keep their stability and biological activity. In this field, ionic liquids (ILs) have gained momentum in the past years, with a relevant number of works reporting their successful use to dissolve, stabilize, extract, and purify proteins. Different approaches in protein-IL systems have been reported, namely, proteins dissolved in (i) neat ILs, (ii) ILs as co-solvents, (iii) ILs as adjuvants, (iv) ILs as surfactants, (v) ILs as phase-forming components of aqueous biphasic systems, and (vi) IL-polymer-protein/peptide conjugates. Herein, we critically analyze the works published to date and provide a comprehensive understanding of the IL-protein interactions affecting the stability, conformational alteration, unfolding, misfolding, and refolding of proteins while providing directions for future studies in view of imminent applications. Overall, it has been found that the stability or purification of proteins by ILs is bispecific and depends on the structure of both the IL and the protein. The most promising IL-protein systems are identified, which is valuable when foreseeing market applications of ILs, e.g., in "protein packaging" and "detergent applications". Future directions and other possibilities of IL-protein systems in light-harvesting and biotechnology/biomedical applications are discussed. This work was developed within the scope of the project CICECO-Aveiro Institute of Materials, UIDB/50011/2020 (DOI 10.54499/UIDB/50011/2020), UIDP/50011/2020 (DOI 10.54499/UIDP/50011/2020), and LA/P/0006/2020 (DOI 10.54499/LA/P/0006/2020), financed by national funds through the FCT/MCTES (PIDDAC). This work was funded by the PRR - Recovery and Resilience Plan and by the NextGenerationEU funds at Universidade de Aveiro, through the scope of the Agenda for Business Innovation “InsectERA” (Project no. 20 with the application C644917393-00000032). P.B. acknowledges La-Caixa junior research ...